Approach to sustainable forestry of indigenous tree species in Northeast Thailand (JIRCAS, 2012)
Contents: Growth performance of indigenous tree species under uneven-aged forest management in Northeast Thailand, a modeling approach to sustainable forest management and preliminary result of coppicing trials in teak plantations in Kanchanaburi, Thailand.